Freedom of labor - Hetmanseva, Nina (VISEGRAD JOURNAL ON HUMAN RIGHTS, 2017)
The article reveals the essence of labor freedom as the central principle of labor law, which is unthinkableoutside the connection of a person with the state, without its state support. Freedom of work is filled with social humanitarian content, since it is the person who acts as a criterion for assessing the level of freedom. This deter- mines the primacy of labor freedom in relation to the state, the duty of the state to provide it.
Свобода праці
Keywords: labor freedom; right to work; state; employee; subjective right; робоча свобода; право на працю; держава; працівник; суб'єктивне право